2012
DOI: 10.2298/avb1203313g
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Ornithobacterium rhinotracheale presence and pathomorphological changes in broiler respiratory organs in intensive broiler production

Abstract: Three flocks of broilers from the epizootiological region of South Banat, Serbia were chosen for examination, one flock with manifestation of respiratory disorders and two control flocks without respiratory disorders. In the flock with manifested respiratory disorders which was marked as flock number one (flock 1), high seroprevalence of specific antibodies for O. rhinotracheale (46%) was found in 30-dayold broiler chickens. The symptoms presented were: depression, reduction in feed consumption and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The lungs may have hemorrhagic lesions, in which blood is eliminated through the mouth [26,27]. Erythrocytes in the airways caused by ORT infection lead to hyperemia with subsequent blood congestion [28].…”
Section: Mode Of Infection and Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lungs may have hemorrhagic lesions, in which blood is eliminated through the mouth [26,27]. Erythrocytes in the airways caused by ORT infection lead to hyperemia with subsequent blood congestion [28].…”
Section: Mode Of Infection and Transmissionmentioning
confidence: 99%
“…Many researchers have used serology to investigate ORT infections, but the results show wide variations. In the poultry industry, the presence of anti-ORT antibodies in chickens has been reported in many countries [2,15,22,24,27,28,36,37,41,52,[55][56][57]. Serology has advantages compared to bacterial isolation, since antibodies persist for several weeks after infection [5,12,53].…”
Section: Serotyping and Detectionmentioning
confidence: 99%
“…The first data relating to disease caused by Ornithobacterium rhinotracheale (ORT) originate from 1991 (van Beek et al, 1994), but the role of this bacterium in the pathology of avian diseases continues to be subject to investigation. Based on experimental investigations (van Empel et al, 1996(van Empel et al, , 1999Marien et al, 2005;Thachil et al, 2009) and field trials (Travers, 1996;De Rosa et al, 1997;Erbeck & McMurray, 1998;Hafez, 1998;Sakai et al, 2000;Sprenger et al, 2000;Zorman-Rojs et al, 2000;van Veen et al, 2000b;Gavrilović et al, 2012) the opinion that ORT is a secondary opportunistic pathogen prevails in the literature. However, Sprenger et al (1998) and van Veen et al (2000a) demonstrated, in experimentally infected turkeys and broilers, respectively, that ORT is a primary pathogen for them.…”
Section: Introductionmentioning
confidence: 99%